Asymmetric [3 + 2] cycloaddition of donor–acceptor aziridines with aldehydes via carbon–carbon bond cleavage. Issue 6 (2nd March 2016) - Liao, Yuting; Liu, Xiaohua; Zhang, Yu; Xu, Yali; Xia, Yong; Lin, Lili; Feng, Xiaoming
Abstract : An enantioselective [3 + 2] annulation of donor–acceptor aziridines with aldehydes utilizing a relay catalyst system of Nd(OTf)3 / N, N ′-dioxide/LiNTf2 has been realized. Abstract : An enantioselective [3 + 2] annulation of donor–acceptor aziridines with aldehydes has been realized using a Nd(OTf)3 / N, N ′-dioxide/LiNTf2 catalyst system, providing various chiral cis -1, 3-oxazolidines in moderate to good yields with high levels of stereocontrol. A relay catalytic process is proposed where LiNTf2 promotes the formation of azomethine ylide intermediates, and a chiral Nd(iii )– N, N ′-dioxide complex accelerates the asymmetric cycloaddition.